Anti-biofilm role of silver nanoparticles on microbial biofilm: An in vitro study on biofilm of heart valves - Ananda S. Mandal; Kumkum Bhattacharyya; Raveendra D. Totad; Hirak Jyoti Raj (Al Ameen Medical College, 2023)
Background: Infective Endocarditis (IE) caused by microbial biofilm is associated with high degree of mortality and morbidity. Of late, silver nano-particles (AgNPs) with a wide range of antimicrobial, anti-biofilm properties are being studied to combat this drug resistance. Objective: Assessment of anti-biofilm role of AgNPs among the potential biofilm producer isolates retrieved by in-vitro study. Methods: Following inclusion and exclusion criteria, some thirty extracted heart valves were considered to be included in the study. Sample collection, transport, storage and processing of samples for aerobic and anaerobic bacteriological culture were done as per standard microbiological guidelines. Biofilm detection assay and antibiofilm efficacy of indigenously prepared carboxy methyl cellulose capped AgNPs sized 9.5nm (CMC-AgNPs-9.5) were studied using Christensen's et al. method. Statistical Analysis: One-way ANOVA and unpaired t-test were used. P≤ 0.05 obtained was considered statistically significant. Results: Majority were Gram-positive (75%) and 91.6% of the microbial isolates were found to be biofilm producers.CMC-AgNPs-9.5were able to effectively eradicate biofilm. Conclusion: AgNPs by their reactive oxygen species (ROS) generation provide new ray of hope for antimicrobial, antibiofilm and prevention strategies. However in vivo study may be done in future to substantiate the present scientific claim further.